CHALLENGING ENVIRONMENTAL EXPOSURES THROUGH DISCRIMINATION LAW IN EUROPE - Refia Kaya (Ankara Avrupa Çalışmaları Dergisi)
Environmental problems continue becoming more apparent in Europe. Many people are exposed to environmental harms such as heatwaves, chemicals, polluted air, and contaminated water. This article aims to discuss whether it is feasible to frame environmental exposures as discrimination issues and if it is feasible whether European discrimination law can be/is used to challenge environmental exposures. For this, both non-legal and legal sources are analysed. The article identifies the possible internal limitations of discrimination law that have been preventing its application in the domain of environment so far. It is argued that discrimination law has a significant potential despite the limited number of legal cases that link environmental exposures and discrimination in Europe.